2017
DOI: 10.1016/j.jaad.2017.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Pigmentary changes in patients treated with targeted anticancer agents: A systematic review and meta-analysis

Abstract: Background The discovery of signaling networks that drive oncogenic processes has led to the development of targeted anticancer agents. The burden of pigmentary adverse events from these drugs is unknown. Objective To conduct a systematic review and meta-analysis of published clinical trials, and determine the incidence and risk of developing targeted therapy-induced pigmentary changes. Methods A comprehensive search was conducted to identify studies reporting targeted therapy-induced pigmentary changes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 105 publications
(34 reference statements)
1
43
0
Order By: Relevance
“…In a few reported cases, hypopigmentation usually appeared after 1 to 3 cycles of therapy and it gradually developed after maximum 6 to 10 cycles (Sideras et al, ). Our case, however, required more time, being anyway in line with a systematic review and meta‐analysis of published clinical trials that reported the time of onset of pigmentary changes in patients treated with targeted anticancer agents, from “immediately” to up to 10 years after initiation of treatment (Dai et al, ; Sideras et al, ). A case of rapid overnight hair and eyebrow depigmentation in a patient affected by renal cell carcinoma during the second cycle of pazopanib was described.…”
supporting
confidence: 57%
“…In a few reported cases, hypopigmentation usually appeared after 1 to 3 cycles of therapy and it gradually developed after maximum 6 to 10 cycles (Sideras et al, ). Our case, however, required more time, being anyway in line with a systematic review and meta‐analysis of published clinical trials that reported the time of onset of pigmentary changes in patients treated with targeted anticancer agents, from “immediately” to up to 10 years after initiation of treatment (Dai et al, ; Sideras et al, ). A case of rapid overnight hair and eyebrow depigmentation in a patient affected by renal cell carcinoma during the second cycle of pazopanib was described.…”
supporting
confidence: 57%
“…However, pigmentary changes in association with EGFR-TKI treatment are rarely reported. 2 Here, we describe an unusual case of slate gray hyperpigmentation associated with osimertinib therapy.…”
Section: Introductionmentioning
confidence: 91%
“…In particular, with molecular-targeted drugs widely used, adverse effects of such treatments including acneiform eruptions, paronychia, xerosis, mucositis, and alopecia are thought to be less severe, but can still be significant (6). Not only can these toxicities severely affect patients' QOL, but in some specific instances, they can be associated with increased response to therapy (7). Therefore, it is of paramount importance that clinicians familiarize themselves with the basic management of the adverse effects caused by these drugs.…”
mentioning
confidence: 99%